2020
DOI: 10.3390/foods9121791
|View full text |Cite
|
Sign up to set email alerts
|

Improving Polyphenolic Compounds: Antioxidant Activity in Chickpea Sprouts through Elicitation with Hydrogen Peroxide

Abstract: Elicitation appears to be a promising alternative to enhance the bioactive compound content and biological activities of legume sprouts. Multi-response optimization by response surface methodology (RSM) with desirability function (DF) was used to optimize the elicitor concentration (hydrogen peroxide (H2O2)) and germination time in order to maximize total phenolic content (TPC), total flavonoids content (TFC), and antioxidant activity (AOX) of chickpea sprouts. Chemical, antinutritional, and nutraceutical prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 49 publications
1
11
0
2
Order By: Relevance
“…This may be related to a better functioning of secondary metabolism over time, as reported in two-step in vitro production systems [42]. In this sense, the elicitation effect of exogenous H2O2 on the secondary metabolism has been reported in numerous systems [43][44][45]. On the other hand, culture in liquid medium provided higher anthocyanin concentrations-an order of magnitude higher-than those observed on solid media (Figure 2), as reported in [25,46].…”
Section: Resultssupporting
confidence: 56%
“…This may be related to a better functioning of secondary metabolism over time, as reported in two-step in vitro production systems [42]. In this sense, the elicitation effect of exogenous H2O2 on the secondary metabolism has been reported in numerous systems [43][44][45]. On the other hand, culture in liquid medium provided higher anthocyanin concentrations-an order of magnitude higher-than those observed on solid media (Figure 2), as reported in [25,46].…”
Section: Resultssupporting
confidence: 56%
“…The bioactive compounds of Medicago have gotten a lot of interest because of their antibacterial, anti-inflammatory, anticancer, and antioxidant properties [ 7 ]. These biological actions, which include anti-inflammatory and antioxidant properties, may be due to the presence of phenolic and flavonoids chemicals, which function as free radical scavengers and/or metal chelators [ 43 ]. Caunii et al (2012) [ 44 ] found that the lucerne extract included a number of free hydroxyl groups (hydrogen donors), giving the product a significant antioxidizing effect in the human body.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence of increasing the antioxidant metabolites in Cymbopogon proximus sprouts, higher antioxidant activities were observed, as indicated by different antioxidant assays (FRAP, ORAC, DPPH) (Figure 1). Antioxidant activity is considered a key indicator of the nutritive value in edible plant parts [53]. In this regard, the antioxidant capacities of essential oils of Cymbopogon proximus have been previously reported [15].…”
Section: Phenolic Compound Accumulation By Laser Treatment Improved the Overall Antioxidant Capacity Of Cymbopogon Proximus Sproutsmentioning
confidence: 99%
“…assays (FRAP, ORAC, DPPH) (Figure 1). Antioxidant activity is considered a key indicator of the nutritive value in edible plant parts [53]. In this regard, the antioxidant capacities of essential oils of Cymbopogon proximus have been previously reported [15].…”
Section: Phenolic Compound Accumulation By Laser Treatment Improved the Overall Antioxidant Capacity Of Cymbopogon Proximus Sproutsmentioning
confidence: 99%